COMBINATION OF SAW-TOPSIS AND BORDA COUNT METHODS IN SEQUENCING POTENTIAL CONVALESCENT PLASMA DONORS - Ilmiyah, Nur Fadilatul; Al Hasani, Salma Zahrotun Nihayah; Renaningtyas, Della (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Convalescent Plasma Therapy (CPT) is an additional therapy to increase the chances of recovery for patients infected with COVID-19. CPT is carried out by giving blood plasma from COVID-19 survivors to COVID-19 patients. Not all survivors of COVID-19 can become plasma donors. Several criteria must be met. Therefore, selecting and sequencing potential plasma donors can be considered an act of decision-making. This research aims to provide an overview of the application of the SAW-TOPSIS combination and the Borda Count method in selecting and ranking potential plasma donor candidates. The criteria for prospective plasma donors are limited to six aspects, namely age, weight, history of blood transfusion, gender, pregnancy status, history of being infected with COVID-19, and history of previous illnesses. Data was taken from ten COVID-19 survivors to illustrate the application of the three methods. The data is taken from a questionnaire distributed via Google Forms. This research was carried out through 3 stages: applying the SAW method, the TOPSIS method, and the Borda Count method. From the calculated results, P06 was the most potential plasma donor candidate, followed by P03, P09, P02, and P04.